An alternative method for the regio- and stereoselective bromination of alkenes, alkynes, toluene derivatives and ketones using a bromide/bromate couple - Adimurthy, Subbarayappa; Ghosh, Sudip; Patoliya, Paresh U.; Ramachandraiah, Gadde; Agrawal, Manoj; Gandhi, Mahesh R.; Upadhyay, Sumesh C.; Ghosh, Pushpito K.; Ranu, Brindaban C. (Green chemistry : an international journal and green chemistry resource : GC, 2008)
An alternative method for the regio- and stereoselective bromination of alkenes, alkynes, toluene derivatives and ketones using a bromide/bromate couple was developed. The main impurity formed in the course of PNBBR synthesis was the dibromo impurity, as confirmed through gas chromatography-mass spectrometry (GC-MS). The alkene or alkyne was stirred with the bromide-bromate couple, NaBr-NaBrO sub(3) (BR-A), in acetic acid at room temperature for a certain period of time (TLC). The primary advantage offered by the present reagent was its calculated release of Br sub(2) or BrOH on demand in the reaction vessel without polluting the environment. The selectivity, yield, and simplicity of operation associated with this green brominating agent made it a practical and better alternative to the existing reagents used for these reactions.